Political education at Lorenzo Milani’s School in Barbiana - Krajewska, Anna (Acta Paedagogica Vilnensia, 2016)
The political education of Lorenzo Milani in Barbiana was an education for peace. Its main goal was to shape a learner – an individual not guided by violence, i.e., one who believes in himself/herself and in other people, who has a creative attitude to the surrounding reality and the capacity to modify it in a more human manner. It was also supposed to form a man committed to solving conflicts without the use of violence, through the ability of persuasion, and who would keenly participate in voting and organizing a strike. Milani taught his pupils to “walk a tightrope” by helping them think independently and listen to their own conscience. On the other hand, he thought how to become free, independent citizens, able to discuss issues concerning injustice according with their own beliefs. From the ethical and political point of view, an education of peace was simultaneously an education of change and justice, solidarity, the coexistence of cultures and nations. The education of peace, proposed by Milani, emphasized the ability of learners and the supporters of various political parties to discuss and – above all – coexist one with another.
Keywords: Lorenzo Milani; Barbiana; school; politics; political education; community involvement; education for peace